Financial Feasibility of Water Conservation in Agriculture. Issue 3 (4th March 2021) - Siderius, Christian; Biemans, Hester; Conway, Declan; Immerzeel, Walter; Jaegermeyr, Jonas; Ahmad, Bashir; Hellegers, Petra
Abstract: Global water use for food production needs to be reduced to remain within planetary boundaries, yet the financial feasibility of crucial measures to reduce water use is poorly quantified. Here, we introduce a novel method to compare the costs of water conservation measures with the added value that reallocation of water savings might generate if used for expansion of irrigation. Based on detailed water accounting through the use of a high‐resolution hydrology‐crop model, we modify the traditional cost curve approach with an improved estimation of demand and increasing marginal cost per water conservation measure combination, adding a correction to control for impacts on downstream water availability. We apply the method to three major river basins in the Indo‐Gangetic plain (Indus, Ganges and Brahmaputra), a major global food producing region but increasingly water stressed. Our analysis shows that at basin level only about 10% (Brahmaputra) to just over 20% (Indus and Ganges) of potential water savings would be realized; the equilibrium price for water is too low to make the majority of water conservation measures cost effective. The associated expansion of irrigated area is moderate, about 7% in the Indus basin, 5% in the Ganges and negligible in the Brahmaputra, but farmers' gross profit increases more substantially, by 11%. Increasing the volumetric cost of irrigation water influences supply and demand in a similar way and has little influence on water reallocation. Controlling for the impact on return flows is important and more than halves the amount of water available for reallocation. Plain Language Summary: A number of water conservation measures in agriculture have been proposed to produce more food with less water. However, the extent to which the benefits—the value of additional crop production supported by water savings—compensate the costs of these measures is poorly quantified. A complicating factor is that losses from inefficient use of water upstream are often reused downstream so that benefits of water conservation measures tend to be overstated. We used detailed model simulations to trace the impact of various measures on all irrigation water fluxes, including these losses, and crop production and its value. We then compared the cost of water conservation with the demand for water in three major river basins; the Indus, Ganges and Brahmaputra. We show that only just over 20% of potential water savings would be realized if financial feasibility is taken into account; the majority of water conservation measures are simply too costly. Despite these limited water savings and the modest expansion of irrigation they would allow, their implementation would improve farm profits in a region where the profitability of farming is low. Key Points: A novel method compares the costs of water conservation measures with the added value that reallocation of water in agriculture generates Only 10%–20% of potential water savings would be realized in the Indo‐Gangetic plain if financial feasibility is taken into account Despite the modest expansion of irrigation it would accommodate, investing in water conservation can add significant profit to agriculture